First records of the sugar cane and forage grass pest, Prosapia simulans (Homoptera: Cercopidae), from South America - Peck, DC; Castro, U.; López, F.; Morales Rodriguez, A.; Rodríguez Chalarca, Jairo (2001)
The genus Prosapia Fennah and P. simulans (Walker) are reported for the first time in South America, based on recent field collections in Colombia and museum specimens from Venezuela. Prosapia simulans was found on Axonopus micay García-Barr., Brachiaria decumbens Stapf, B. dictyoneura (Fig. & De Not.) Stapf, Cynodon plectostachyus (K. Schum.) Pilger, Hyparrhenia rufa (Nees) Stapf and Saccharum officinarum L. (Poaceae). Persistent field populations were detected from 1060-1621 m elevation, principally associated with B. decumbens, reaching economic levels in one of the observed sites. On two occasions P. simulans was found on sugar cane. Evidence suggests that this Central American sugar cane and forage grass pest is a well-established new arrival, thereby representing a new threat to pasture production and potential threat to cane production in Colombia's Cauca Valley. The distribution, bionomics, and pest status of P. simulans are summarized, and its mode of introduction and potential pest status are discussed.